Disagreement and forms of politeness in Moroccan media debate: An interactional approach - Azouzi, Hassan (Taikomoji kalbotyra, 2024)
This study aims explores the concept of disagreement in Moroccan media debates during the COVID-19 pandemic. It aims to analyse how disagreement is expressed and the forms it takes in the context of confrontational televised debates. Drawing on the framework of ethnomethodological conversational analysis, disagreement is viewed as a reactive act that is conditionally dependent on the speaker‘s initiating act. Recognising the potential risks of their respective acts, participants in these verbal interactions employ softeners and/or emphatics to mitigate or intensify their responses, striving to avoid outright rudeness when expressing disagreemnt. The analysis is based on a substantial corpus of transcribed and aligned speech, enabling the identification of key elements that shape responses in this context.